Kresoxim-methyl primes Medicago truncatula plants against abiotic stress factors via altered reactive oxygen and nitrogen species signalling leading to downstream transcriptional and metabolic readjustment - Filippou, Panagiota S.; Antoniou, Chrystalla; Obata, Toshihiro; Van Der Kelen, Katrien; Harokopos, Vaggelis; Kanetis, Loukas; Aidinis, Vassilis; Van Breusegem, Frank; Fernie, Alisdair; Fotopoulos, Vasileios (My University, 2016)
Published by Oxford University Press on behalf of the Society for Experimental Biology.Biotic and abiotic stresses, such as fungal infection and drought, cause major yield losses in modern agriculture. Kresoxim-methyl (KM) belongs to the strobilurins, one of the most important classes of agricultural fungicides displaying a direct effect on several plant physiological and developmental processes. However, the impact of KM treatment on salt and drought stress tolerance is unknown. In this study we demonstrate that KM pre-treatment of Medicago truncatula plants results in increased protection to drought and salt stress. Foliar application with KM prior to stress imposition resulted in improvement of physiological parameters compared with stressed-only plants. This protective effect was further supported by increased proline biosynthesis, modified reactive oxygen and nitrogen species signalling, and attenuation of cellular damage. In addition, comprehensive transcriptome analysis identified a number of transcripts that are differentially accumulating in drought- and salinity-stressed plants (646 and 57, respectively) after KM pre-treatment compared with stressed plants with no KM pre-treatment. Metabolomic analysis suggests that the priming role of KM in drought- and to a lesser extent in salinity-stressed plants can be attributed to the regulation of key metabolites (including sugars and amino acids) resulting in protection against abiotic stress factors. Overall, the present study highlights the potential use of this commonly used fungicide as a priming agent against key abiotic stress conditions.
Keywords: Drought; Priming; Reactive species; Salinity; Strobilurins; Systems biology